Argumentation by Analogy and Weighing of Reasons - Alhambra, José (Informal Logic, 2022)
John Woods and Brent Hudak’s theory on arguments by analogy (1989), although correct in its meta-argumentative approach, gives rise to problems when we consider the possibility of weighing reasons. I contend that this is an outcome of construing the relationship between the premises and the conclusion of arguments compared in argumentation by analogy as inferences. An interpretation in terms of reasons is proposed here. The reasons-based approach solves these problems and allows the theory to be extended to account for a particular variant of argumentation by analogy in which the subjects of comparison are not arguments, but weighings of reasons.